Mathematical foundations of image processing and analysis 1 - Pinoli, Jean-Charles (ISTE Ltd/John Wiley and Sons Inc, 2014)
This book aims to introduce a comprehensive and convenient overview of the key mathematical concepts, notions, tools and frameworks involved in the various fields of gray-tone and binary image processing and analysis. the textbook split over two volumes, made up of 7 main parts divided into 40 chapters and sub-divided into 207 sections